(untitled) (Journal of Pure and Applied Sciences (Science Forum), 2025)
The study area is located in Northeastern Nigeria. It lies between longitudes 12° 52’30” and 12°59’30” E, and latitudes 10° 07’00” and N 10° 16’00”. It is about 116 km2 in areal extent and lies in the south central of Hawal Massif. It is bounded to the west and south by the Gongola and Yola arms of the Benue Trough. Northwards, it is bounded by the Chad Quaternary Basin. The major rock units in the study area include fine to coarse grained granites, fine grained granites syenite, and quartz syenite. The rocks are characterized by a wide range in SiO2 (58.7- 73.0 wt.%,), alkaline to Calc-alkaline affinity, syn- to late orogenic signatures, metaluminousto peralkaline composition. The granitoids in the study area are categorized into alkaline and calc- alkaline suite based on their geochemical characteristics. The high K2O and Na2O (4.86- 6.99wt.% and 4.62-6.98 wt.%. respectively) and low Y/Nb ratio of < 2 for the alkaline suites are typical of granitoid suites that are commonly considered as derivatives of mantle sources. All these data indicate that the rocks in the study area are probably formed from fractional crystallization of magmas derived from the lithospheric mantle, which emplaced the syenites, quartz syenite and alkaline granites. The calc-alkaline granite is characterized by higher SiO2 compositionand Y/N ratio >2 exhibiting crustal affinity that was probably formed by the melting of the lower crust. This study indicates that the area under study was affected by two major tectonic (magmatic), which suggest that the calc alkalic granitoids were emplaced earlier during syn-collision by partial melting of Paleoproterozoic crust. Magmatism during the second tectonic episode resulted in to the emplacement of the alkaline granitoids via fractional crystallization and crustal assimilation of lithospheric mantle melts in the late orogenic stage. These rocks exhibit dominantly NNE-SSW structural trend comparable those of othe Pan African granitoids in Nigeria. Additional trace element geochemistry, geochronology and isotopic studies are required to ascertain the origin, age and mineral potentials of the distinct rock suites found in this study area.